2013
DOI: 10.5946/ce.2013.46.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Barrett's Esophagus and Esophageal Carcinoma

Abstract: This paper reviews the use of photodynamic therapy (PDT) in patients with Barrett's esophagus and esophageal carcinoma. We describe the history of PDT, mechanics, photosensitizers for PDT in patients with esophageal disease. Finally, we discuss its utility and limitations in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 88 publications
0
50
0
1
Order By: Relevance
“…This generates various cytotoxic reactive oxygen species such as singlet oxygen that can interact with and damage cellular components, leading to cell death. Many photosensitisers have been developed and have received approval or clinical trials for use in the treatment of cancer, 2 age-related macular degeneration, 3 pre-cancerous conditions such as Barret's oesphagus, 4 and oral sterilisation in dental procedures. 5 Among these, porphyrins and other tetrapyrrole-related compounds remain the broadest class of compound under study for PDT and other light-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This generates various cytotoxic reactive oxygen species such as singlet oxygen that can interact with and damage cellular components, leading to cell death. Many photosensitisers have been developed and have received approval or clinical trials for use in the treatment of cancer, 2 age-related macular degeneration, 3 pre-cancerous conditions such as Barret's oesphagus, 4 and oral sterilisation in dental procedures. 5 Among these, porphyrins and other tetrapyrrole-related compounds remain the broadest class of compound under study for PDT and other light-based therapies.…”
Section: Introductionmentioning
confidence: 99%
“…PDT has clinical applications in the treatment of a variety of solid cancers [4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], including but not limited to those of lung, skin, breast, head and neck, digestive tract, pancreas, liver, bladder, ovary, prostate and brain. In addition, there are many clinical applications of PDT for treatment of a wide range of non-cancerous conditions, such as bacterial and fungal infections; hyperproliferative or inflammatory conditions, such as macular degeneration or psoriasis; and premalignant conditions, such as actinic keratosis [22] and Barrett's esophagus [23]. To achieve better therapeutic efficacy, new photosensitizers and novel light sources are continuously being developed, and the mechanisms of action are becoming better understood [24,25].…”
mentioning
confidence: 99%
“…12 WST11-VTP differs from classical PDT 20-26 and offers major advantages, including absence of prolonged skin photosensitivity, which has been a major barrier to widespread utilization of traditional PDT. 22-24 WST11-VTP has been successfully and safely applied in phase II clinical trials for tissue ablation in cancer bearing organs. 14,15 Results from studies In prostate cancer have shown well-preserved quality of life, indicating the potential to overcome the disadvantages of other ablation approaches.…”
Section: Discussionmentioning
confidence: 99%